PLANT GROWTH PROMOTING RHIZOBACTERIA (PGPR) DARI AKAR BAMBU APUS (Gigantochola apus) MENINGKATKAN PERTUMBUHAN TANAMAN - Elza Yulistiana; Hening Widowati; Agus Sutanto (BIOLOVA, 2020)
Abstract: Living things need nutrients to grow and their endurance. The presence of nutrients around plant roots is very important for microorganisms as biological control agents and also for plant pathogens. PGPR Plant Growth Promoting Rhizobacteria (PGPR) has a role in increasing plant growth, crop yields and plant growth. Bacteria in PGPR can actively colonize the rhizosphere. Bamboo roots are colonized by many bacteria (Pseudomonas fluorescens), these bacteria can play a role in increasing the solubility of P in the soil, certain strains of Pseudomonas sp. can prevent plants from fungal pathogens that come from the soil. Rhizobacteria from the Bacillus spp. and Pseudomonas spp., able to dissolve phosphate, while the Serratia spp. group, in addition to being able to increase the availability of P (phosphate) can also fix nitrogen and be able to synthesize IAA. Microbes with the ability to produce phytohormone are an effort to help in increasing plant growth.